Solidago ×snarskisii nothosp. nov. (Asteraceae) from Lithuania and its position in the infrageneric classification of the genus - Gudžinskas, Zigmantas; Žalneravičius, Egidijus (Phytotaxa, 2016)
A natural hybrid between the native Solidago virgaurea and the alien invasive S. gigantea, recorded in South Lithuania, is described as S. ×snarskisii nothosp. nov. A new nothosubsection, Solidago sect. Solidago nothosubsect. Triplidago nothosubsect. nov., is proposed to accommodate this hybrid and S. ×niederederi.